Role of MicroRNA in linking diabetic retinal neurodegeneration and vascular degeneration - Zhao, Haiyan; Cai, Yichen; Pan, Junhua; Chen, Qiu (Frontiers in Endocrinology, 2024)
Diabetic retinopathy is the major cause of blindness in diabetic patients, with limited treatment options that do not always restore optimal vision. Retinal nerve degeneration and vascular degeneration are two primary pathological processes of diabetic retinopathy. The retinal nervous system and vascular cells have a close coupling relationship. The connection between neurodegeneration and vascular degeneration is not yet fully understood. Recent studies have found that microRNA plays a role in regulating diabetic retinal neurovascular degeneration and can help delay the progression of the disease. This article will review how microRNA acts as a bridge connecting diabetic retinal neurodegeneration and vascular degeneration, focusing on the mechanisms of apoptosis, oxidative stress, inflammation, and endothelial factors. The aim is to identify valuable targets for new research and clinical treatment of diabetic retinopathy.